Diagnosing new-onset asthma in a paediatric clinical trial setting in school-age children - Roberts, Graham; Valovirta, Erkka; Halken, Susanne; Eng, Peter A.; Mäkelä, Mika J.; Carlsen, Karin C. Lødrup; Knecht, Roland; Malmberg, L. Pekka (FRONTIERS MEDIA SA, 2025)
Asthma is a common chronic disease in children. It is a dynamic condition-symptoms change over time, and the outcome of diagnostic tests can vary. Consequently, evaluating the onset of asthma at a single point in time, perhaps when patients are asymptomatic with limited impairment of the lung function, may result in false diagnostic conclusions. The absence of consistent gold-standard diagnostic criteria in children challenges the ability of any study to ascertain an effect of treatment on asthma prevention. A comprehensive review of the diagnostic criteria used for new-onset asthma in school-age children was conducted based on existing recommendations from published clinical guidance, alongside evidence from paediatric asthma prevention trials. Findings from the review were used to propose suggestions for diagnosing new-onset asthma in future asthma prevention trials. Despite an overall lack of consensus in the published clinical guidance, there are similarities between the various recommendations for diagnosing asthma in children, which typically involve assessing the variable symptoms and supplementing the medical history with objective measures of lung function. For future paediatric asthma prevention trials, we suggest that paediatric clinical trials should use a new-onset asthma definition that incorporates the concepts of "possible", "probable" and "confirmed" asthma. "Possible" asthma would capture self-reported features of chronic symptoms and symptom relief with beta 2-agonist bronchodilator (suggesting reversibility). "Probable" asthma would include symptom chronicity, self-reported symptom relief with beta 2-agonist bronchodilator, and objective features of asthma (reversibility or bronchial hyper-responsiveness). A "confirmed" diagnosis would be made only if there is a positive response to controller therapy. These suggestions aim to improve the diagnosis of new-onset childhood asthma in clinical trials, which will be useful in the design and conduct of future paediatric asthma prevention trials.